STUDY ON IMPLEMENTATION OF CONSTRUCTION WASTE MANAGEMENT IN MINIMIZING CONSTRUCTION MATERIAL WASTE - Haryo Aji Kurniawan; Fajar Susilowati; Ria Miftakhul Jannah (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
The implementation of a building construction project is unavoidable from the emergence of waste material. Construction material waste is defined as something that is over what is required. This study intends to find the application of construction waste management in building construction projects to minimize the waste material. Data was collected using observation, interviews, and distributing questionnaires to 4 building project parties in Central Java using a random sampling method. Data analysis was carried out by descriptive analysis to determine the type and cause of the highest waste material and supported by regression and correlation analysis to assess the application of ways to minimize waste material. The results of data analysis show that the most types of waste material are formwork wood, reinforcing steel, concrete, and cement. The factor causing waste material that most often occurs is the design change factor that comes from the design phase. Based on the analysis, the effort to minimize waste material that is the most influential on it is improving the quality of tool and material management by providing training to construction personnel related to materials construction used